Strengthening Policy Dialogue on Environment : Learning from Five Years of Country Environmental Analysis - Pillai, Poonam (World Bank, Washington, DC, 2014)
The objective of this paper is to review experience with completed country environmental analysis (CEAs) to improve the effectiveness of CEAs as a strategic analytical tool. Through in-depth analysis of the process, methodologies, costs, and results of completed CEA pilots, the paper assesses how effective CEAs have been in informing and providing strategic guidance to the Bank and client countries on environment-development issues and the extent to which they have facilitated donor coordination. The analysis carried out in this paper also provides feedback on when to prepare a CEA, how to prepare and structure CEAs, and how to use specific methodologies and processes in influencing policy dialogue with partner countries. The findings are of potential interest to World Bank sector managers, country directors, CEA task teams, and environmental staff, but also to development partners who carry out work similar to CEAs. The paper is based on a desk review of completed CEAs and on interviews with task managers and members of CEA teams. Several reports, including a fieldwork-based assessment of the Ghana, India, and Guatemala CEAs commissioned by the Environment Department; a review on Tunisia by the Quality Assurance Group (QAG); and a report commissioned by the Latin America and Caribbean Region, based on in-country assessments of completed CEAs, have also informed this study. A detailed case study analysis of each completed CEA was prepared for this exercise; it substantively informed the review and is available as a background paper. The original CEA concept note proposed that CEAs have three main building blocks: (a) establishment of environment-development priorities linked with growth and poverty reduction, (b) assessment of the environmental implications of sector policies, and (c) institutional analysis. Assessing CEAs against this building block structure, the review highlights several findings.